Climate change disclosures: An examination of Canadian oil and gas firms (Issues in Social and Environmental Accounting (ISEA), 2011)
The purpose of this paper is to examine: (1) to what extent Canadian oil and gas firms have adhered to the Canadian Institute of Chartered Accountant proposed guidelines respecting climate change disclosures in their annual reports, and (2) whether the disclosures of these firms can be influenced by their media visibility, the presence and operating characteristics of an environmental committee within the board of directors, their ownership structure, their audit firms, their political exposure and media visibility. The results show that the level of disclosure is very low; however, when the board of directors has an environment committee, the level of disclosure is higher. This is also the case for firms having significant political exposure and strong media visibility, and for those with a widely held ownership structure. Whether or not the audit firm is one of the Big Four, does not make any difference in the level of disclosure